2017
DOI: 10.1111/jcpt.12519
|View full text |Cite
|
Sign up to set email alerts
|

Role of pharmaceutical care for self-administered pulmonary tuberculosis treatment in Thailand

Abstract: Pharmaceutical care, home visit and modified DOT are all associated with high success rate for pulmonary TB treatment and exceeded the WHO target, in this retrospective analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…We identified nine studies with outcome orientations of improving TB treatment outcomes [ 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Of these, four focused on community pharmacy services and five on hospital services.…”
Section: Resultsmentioning
confidence: 99%
“…We identified nine studies with outcome orientations of improving TB treatment outcomes [ 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Of these, four focused on community pharmacy services and five on hospital services.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study has shown that TB treatment success rates for pharmaceutical care are very similar to those for home visit or modified DOT [ 7 ]. This cost analysis shows that the pharmaceutical care approach is a relatively simple strategy that requires less healthcare resources and costs compared with the other two approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This research was a part of a retrospective cohort study in which the result on the comparative effectiveness of pharmaceutical care versus to home visit and modified DOT was previously publish in the Journal of Clinical Pharmacy and Therapeutics [ 7 ], whereas this study focused on health care resource uses and costs associated to those three different strategies. The material regarding study participants was reproduced from the published article [ 7 ] with permission from the copyright owner (John Wiley and Sons).…”
Section: Transparency Declarationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmaceutical care provides pharmacist-led patient education at every outpatient visit, home visit provide regular home visit until treatment completion, and SAT is an approach where patients take medications by themselves at home without any additional supportive approach (see Online Appendix Table 1 for a description of these strategies). The treatment regimen was described in our previous retrospective cohort study [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%